Origin and function of the yolk sac in primate embryogenesis - Connor Ross (Nature Portfolio, 2020)
Why do human embryos need a yolk sac and how does it form? This Perspective by Thorsten Boroviak and Connor Ross explores the development and function of the yolk sac in primate embryogenesis.